Competency-Based Model of Human Resource Development in Higher Education - Ramly, Amir Tengku; Handrianto, Budi; Syaiful (Jurnal Manajemen, 2024)
This research aims to find the model that best suits the development of Human Resources (HR) in higher education based on the competencies determined by the Indonesian National Work Competency Standards (SKKN). Until now, HR competency standards in higher education have not been standardized, making it difficult to prepare HR development models. Meanwhile, various HR development models are being implemented by the industrial sector. Meanwhile, human resource development in higher education still focuses only on lecturers. There are educational staff (tendik) who are human resources that also need to be developed. The research was conducted using qualitative methods through literature reviews and interviews with HR experts in organizations, companies and the academic world. The results were analyzed using SWOT (Swot Analysis) and decided by experts in a Focus Group Discussion (FGD). The results of this research found important variables that were mapped to the tree structure, namely root variables, stem variables, and fruit/leaf variables